General Issues of Applications Architecture Domain Design - Andrii Kopp; Dmytro Orlovskyi; Dorukhan Ersoyleyen (Zien Journals, 2021)
Applications architecture domain as a part of enterprise architecture is the baseline of any organizational activity, which main goal is to provide the executional environment for business processes in order to deliver products or services to satisfy customer needs and generate revenue. Nowadays, software engineering projects always begin with the architecture design phase, despite the waterfall or agile methodology is used by a software development team. Applications architecture design is the most important and, at the same time, the most error-prone stage of the whole software engineering project. It is well-known, that design shortcomings made on the applications design phase may increase drastically to testing and maintenance phases. Further costs to defects fixing may be hundred times higher in the later project stages in compare to the design stage on which applications architecture is defined.
Keywords: Applications Architecture; Software Development Lifecycle; Software Engineering; Software Design